Foreign Direct Investment in Nepal - Pyakurel, Biraj (NUTA Journal, 2018)
Foreign Direct Investment (FDI) is an important source of capital for economic growth in developing countries. It provides a package which constitutes new technologies, management techniques, finance and market access for the production and movement of goods and services. However, attracting FDI is a major challenge for host countries as it faces the challenge of identifying the major factors that motivate and affect the FDI location decision. The main FDI location factors are cost, market infrastructure, and technological, political, legal and socio-cultural factors. Despite several conflicting circumstances, Nepal is attempting to sort out overarching issues of FDI concerning with economic development. That’s why Nepal is at a point where from it can excel for economic goals via FDI. The set trends illustrate that various indicators pertaining to FDI in the country has been improving since peace process was begun in 2006. This analysis comes to conclusions that the country owns unique advantages and, thereby, opportunities of FDI useful for the country’s prosperity. Yet FDI in the country is not free of challenges, thus, that need to be timely addressed with prudent measures.